Response Assessment to Neoadjuvant Treatment with Dual HER2 Blocker in HER2 positive Early and Locally Advanced Breast Cancer - Bashir, Asima; Nadeem, Muhammad; Nasir, Maimoona; Bangash, Mussavir Hussain; Khattak, Rahimullah; Khan, Amjad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To analyze response assessment to dual HER2 blockade in HER2 positive early and advanced breast cancer and to identify factors associated with partial response among the study participants Study Design: Quasi-experimental study. Place and Duration of Study: Oncology Department, Combined Military Hospital Rawalpindi, Pakistan, from Sep 2022 to Apr 2023. Methodology: One hundred and eighty ladies with early and advanced breast cancer who were HER2 neu positive and were given dual HER2 blockade treatment before surgical resection of the tumor. Response was assessed after the surgery on surgical specimen and classed as partial or complete response. Relevant clinical factors were associated with presence of partial response among the women included in the study. Results: Mean age of the patients was 45.56±9.91 years. Out of 180 patients, 116(32.9%) had complete pathological response while 64(25.6%) had partial response to the neo-adjuvant therapy combined with dual HER2 blockade. Having T1-2N1 disease, ER PR negative and HER2 positive disease, and not having interruptions in treatment due to neutropenia or cardiotoxicity were found associated with complete pathological response to neo-adjuvant medications combined with dual HER2 blockade (p-value<0.05). Conclusion: Complete pathological response was seen in the majority of patients included in our study. Having T1-2N1 disease, ER PR negative and HER2 positive disease, and not having interruptions in treatment due to neutropenia or cardiotoxicity were factors associated with complete pathological response in our study participants.